Dentifrice formulations containing bioactive glass
By adjusting the composition ratio of bioactive glass, reducing the alkali metal content, the durability of glass in an aqueous environment and the biological activity of saliva are improved, and the problem of insufficient durability and biological activity of traditional bioactive glass in dental cleaning agents is solved. It is suitable for aqueous dental cleaning agent preparations.
Patent Information
- Application Number
- CN202380079749.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-09
- Filing Date
- 2023-11-02
- Publication Date
- 2025-07-08
AI Technical Summary
The existing bioactive glasses are insufficient in aqueous environments, which are difficult to meet the long shelf life requirements of dental cleaner products, and the biological activity of traditional alkali-free compositions is low.
A bioactive glass composition containing a specific proportion of SiO2, CaO, P2O5 and ZrO2 was developed to reduce alkali metal content, improve durability in aqueous solutions, and rapidly convert to apatite in artificial saliva.
It has achieved the improvement of the durability of bioactive glass in an aqueous environment, is suitable for aqueous dental cleaning preparations, and is rapidly converted into apatite in saliva, enhancing biological activity.
Smart Images

Figure CN120282766A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority of U.S. Provisional Application No. 63 / 423,906, filed Nov. 9, 2022, under 35 U.S.C. § 119, the content of which is incorporated herein by reference in its entirety.
[0002] This specification generally relates to bioactive glasses and, more particularly, to dentifrice formulations containing bioactive glasses. Background Art
[0003] Oral diseases constitute a significant health burden worldwide and affect nearly 3.5 billion people throughout their lives, causing pain, discomfort, disfigurement, and even death. Globally, an estimated 2.3 billion people have permanent tooth decay, and over 530 million children have primary tooth decay. Dissolution of apatite crystals and net loss of calcium, phosphate, and other ions from teeth (demineralization) are the cause of tooth decay. Tooth decay can be managed non-invasively through a remineralization process in which calcium and phosphate ions are supplied to the teeth from an external source to promote crystal deposition into voids in demineralized enamel. Crystalline forms of calcium phosphate phases (brushite, β-tricalcium phosphate, octacalcium phosphate, hydroxyapatite, fluorapatite, and enamel apatite) and amorphous forms of calcium phosphate phases are used in the remineralization process. Among these materials, amorphous calcium phosphate (bioactive glass) shows the most promising evidence in the remineralization process. There is an urgent need to develop novel bioactive glass compositions that can promote the remineralization process to prevent or repair tooth decay. Summary of the Invention
[0004] According to an embodiment, a dentifrice formulation comprises: a solvent; a humectant; and a bioactive glass, wherein the bioactive glass comprises: SiO2 in an amount greater than or equal to 15 wt % and less than or equal to 45 wt %, CaO in an amount greater than or equal to 30 wt % and less than or equal to 60 wt %, P2O5 in an amount greater than or equal to 8 wt % and less than or equal to 30 wt %, and ZrO2 in an amount greater than or equal to 2 wt % and less than or equal to 15 wt %.
[0005] According to one or more embodiments, a dentifrice formulation comprises: a solvent; a humectant; and a bioactive glass, wherein the bioactive glass comprises: SiO2 in an amount greater than or equal to 20.0 wt% and less than or equal to 39.5 wt%; MgO in an amount greater than or equal to 0.0 wt% and less than or equal to 14.5 wt%; CaO in an amount greater than or equal to 32.5 wt% and less than or equal to 47.0 wt%; SrO in an amount greater than or equal to 0.0 wt% and less than or equal to 14.5 wt%; ZnO in an amount greater than or equal to 0.0 wt% and less than or equal to 14.5 wt%; P2O5 in an amount greater than or equal to 9.5 wt% and less than or equal to 24.5 wt%; and ZrO2 in an amount greater than or equal to 4.0 wt% and less than or equal to 10.0 wt%.
[0006] According to one or more embodiments, a dentifrice formulation comprises: bioactive glass in an amount greater than or equal to 2 wt% and less than or equal to 15 wt%; a solvent in an amount greater than or equal to 30 wt% and less than or equal to 45 wt%; a humectant in an amount greater than or equal to 40 wt% and less than or equal to 50 wt%; fluoride ions in an amount greater than or equal to 0.2 wt% and less than or equal to 1.0 wt%; a flavoring agent in an amount greater than or equal to 0.5 wt% and less than or equal to 5.0 wt%; a surfactant in an amount greater than or equal to 0.5 wt% and less than or equal to 1.5 wt%; a sweetening agent in an amount greater than or equal to 0.1 wt% and less than or equal to 0.5 wt%; an abrasive in an amount greater than or equal to 2 wt% and less than or equal to 8 wt%; and a whitening agent in an amount greater than or equal to 0.1 wt% and less than or equal to 0.5 wt%.
[0007] Additional features and advantages will be set forth in the detailed description which follows, and in part will be obvious from the description, or may be learned by practice of the embodiments described herein, including the detailed description, the claims as well as the drawings.
[0008] It is to be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the nature and characteristics of the claimed subject matter. Drawings are included to provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The drawings illustrate the various embodiments described herein and together with the detailed description are used to explain the principles and operations of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 Graphically depicts the weight loss over time in water of a bioactive glass composition and a conventional glass composition according to the embodiments disclosed and described herein;
[0010] Figure 2 Graphically depict the weight loss over time of bioactive glass compositions and conventional glass compositions according to the embodiments disclosed and described herein in artificial saliva;
[0011] Figure 3 Scanning electron microscope (SEM) images of a bioactive glass composition according to the embodiments disclosed and described herein before and after exposure to artificial saliva;
[0012] Figure 4 SEM images of a conventional glass composition before and after exposure to artificial saliva;
[0013] Figure 5 A graph showing X-ray diffraction (XRD) data of a bioactive glass composition and a conventional glass composition according to the embodiments disclosed and described herein after exposure to artificial saliva;
[0014] Figure 6 A graph showing XRD data of a bioactive glass composition according to the embodiments disclosed and described herein before and after exposure to artificial saliva;
[0015] Figure 7 A graph showing XRD data of a conventional glass composition before and after exposure to artificial saliva;
[0016] Figure 8 A graph showing XRD data of a bioactive glass composition according to the embodiments disclosed and described herein before and after exposure to artificial saliva;
[0017] Figure 9 A graph showing XRD data of a bioactive glass composition according to the embodiments disclosed and described herein before and after exposure to artificial saliva;
[0018] Figure 10 A graph showing XRD data of a conventional glass composition before and after exposure to artificial saliva;
[0019] Figure 11 A graph showing the pH over time of a bioactive glass composition according to the embodiments disclosed and described herein in artificial saliva and water;
[0020] Figure 12 A graph showing the pH over time of a conventional glass composition in artificial saliva and water;
[0021] Figure 13 A graph showing the normalized loss over time of a bioactive glass composition and a conventional glass composition according to the embodiments disclosed and described herein in artificial saliva and water;
[0022] Figure 14 To show graphs of the normalized loss over time of bioactive glass compositions and conventional glass compositions according to the embodiments disclosed and described herein in artificial saliva and water;
[0023] Figure 15 To show bar graphs of the normalized silicon loss of bioactive glass compositions and conventional glass compositions according to the embodiments disclosed and described herein after exposure to artificial saliva and water; and
[0024] Figure 16 To show bar graphs of the ISO 719 test results of bioactive glass compositions and conventional glass compositions according to the embodiments disclosed and described herein. DETAILED DESCRIPTION
[0025] Reference will now be made in detail to embodiments of bioactive glass and dentifrice formulations containing bioactive glass. Wherever possible, the same reference numerals will be used throughout the drawings to refer to the same or like parts. In the embodiments, the dentifrice formulation comprises: a solvent; a humectant; and a bioactive glass, wherein the bioactive glass comprises: SiO2 in an amount greater than or equal to 15 wt% and less than or equal to 45 wt%, CaO in an amount greater than or equal to 30 wt% and less than or equal to 60 wt%, P2O5 in an amount greater than or equal to 8 wt% and less than or equal to 30 wt%, and ZrO2 in an amount greater than or equal to 2 wt% and less than or equal to 15 wt%.
[0026] Bioactive glass has the recognized ability to firmly bond to hard and soft tissues and promote the growth of osteocytes and chondrocytes. So far, most bioactive glass compositions belong to the Na2O-CaO-SiO2 family. The commercially available bioactive glass 45S5 in this family is registered as U.S. Patent No. 4,234,972. The rapid degradation and conversion to apatite make these alkali metal-containing bioactive glasses attractive for a wide range of applications. However, the low chemical durability of traditional bioactive glasses can be a problem when a long shelf life in an aqueous environment is required. For example, as disclosed in U.S. Patent No. 8,715,625, non-aqueous formulations must be developed to use 45S5 glass particles in dentifrice products. Alkali metal-free bioactive glass compositions in the CaO-SiO2-P2O5 system are disclosed in U.S. Patent No. 5,074,916, but their bioactivity is not as good as that of alkali metal-containing compositions. Therefore, there is a strong need for new aqueous or non-aqueous dentifrice formulations containing bioactive glass for conventional use.
[0027] In the present disclosure, aqueous and non-aqueous dentifrice formulations are provided that contain bioactive glass as an active ingredient. The bioactive glasses disclosed and described herein have significantly improved water durability compared to conventional 45S5 such that it is possible to produce aqueous dentifrice formulations.
[0028] The bioactive glass compositions will now be described in more detail. Compared to traditional 45S5 glass, the bioactive glass compositions disclosed and described herein have a lower alkali metal content, exhibit improved water durability in aqueous solution, and convert to apatite more quickly in artificial saliva.
[0029] Examples of the bioactive glasses disclosed and described herein include silica (SiO2) in an amount greater than or equal to 15 weight percent (wt%) and less than or equal to 45 wt%, calcium oxide (CaO) in an amount greater than or equal to 30 wt% and less than or equal to 60 wt%, phosphorus pentoxide (P2O5) in an amount greater than or equal to 8 wt% and less than or equal to 30 wt%, and zirconium dioxide (ZrO2) in an amount greater than or equal to 2 wt% and less than or equal to 15 wt%. The bioactive glass compositions may also optionally include magnesium oxide (MgO) in an amount less than or equal to 25 wt%, strontium oxide (SrO) in an amount less than or equal to 10 wt%, zinc oxide (ZnO) in an amount less than or equal to 10 wt%, boron trioxide (B2O3) in an amount less than or equal to 5 wt%, aluminum oxide (Al2O3) in an amount less than or equal to 5 wt%, lithium oxide (Li2O) in an amount less than or equal to 10 wt%, sodium oxide (Na2O) in an amount less than or equal to 10 wt%, potassium oxide (K2O) in an amount less than or equal to 10 wt%, and fluoride ions (F - )
[0030] Relative to other bioactive glass compositions, a lower SiO2 content is believed to improve the bioactivity of the bioactive glass compositions disclosed and described herein. SiO2, an oxide involved in glass formation, can also be used to stabilize the network structure of glasses and glass-ceramics. The amount of SiO2 can be limited to control the melting temperature of the glass, since the melting temperature of pure SiO2 or high-SiO2 glasses is undesirably high. In embodiments, the bioactive glass composition comprises from greater than or equal to 15 wt% to less than or equal to 45 wt% SiO2, such as from greater than or equal to 20 wt% to less than or equal to 45 wt% SiO2, from greater than or equal to 25 wt% to less than or equal to 45 wt% SiO2, from greater than or equal to 30 wt% to less than or equal to 45 wt% SiO2, from greater than or equal to 35 wt% to less than or equal to 45 wt% SiO2, from greater than or equal to 40 wt% to less than or equal to 45 wt% SiO2, from greater than or equal to 15 wt% to less than or equal to 40 wt% SiO2, from greater than or equal to 20 wt% to less than or equal to 40 wt% SiO2, from greater than or equal to 25 wt% to less than or equal to 40 wt% SiO2, from greater than or equal to 30 wt% to less than or equal to 40 wt% SiO2, from greater than or equal to 35 wt% to less than or equal to 40 wt% SiO2, from greater than or equal to 15 wt% to less than or equal to 35 wt% SiO2, from greater than or equal to 20 wt% to less than or equal to 35 wt% SiO2, from greater than or equal to 25 wt% to less than or equal to 35 wt% SiO2, from greater than or equal to 30 wt% to less than or equal to 35 wt% SiO2, from greater than or equal to 15 wt% to less than or equal to 30 wt% SiO2, from greater than or equal to 20 wt% to less than or equal to 30 wt% SiO2, from greater than or equal to 25 wt% to less than or equal to 30 wt% SiO2, from greater than or equal to 15 wt% to less than or equal to 25 wt% SiO2, from greater than or equal to 20 wt% to less than or equal to 25 wt% SiO2, or from greater than or equal to 15 wt% to less than or equal to 20 wt% SiO2.
[0031] A relatively high CaO content and a relatively low SiO2 compared to other bioactive glass compositions are believed to improve the bioactivity of the bioactive glass compositions disclosed and described herein. CaO also reduces the viscosity of the glass, which enhances formability, strain point, and Young's modulus. However, when too much CaO is added to the bioactive glass composition, the density and CTE of the bioactive glass composition increase. In an embodiment, the bioactive glass composition comprises from greater than or equal to 30 wt% to less than or equal to 60 wt% of CaO, such as from greater than or equal to 35 wt% to less than or equal to 60 wt% of CaO, from greater than or equal to 40 wt% to less than or equal to 60 wt% of CaO, from greater than or equal to 45 wt% to less than or equal to 60 wt% of CaO, from greater than or equal to 50 wt% to less than or equal to 60 wt% of CaO, from greater than or equal to 55 wt% to less than or equal to 60 wt% of CaO, from greater than or equal to 30 wt% to less than or equal to 55 wt% of CaO, from greater than or equal to 35 wt% to less than or equal to 55 wt% of CaO, from greater than or equal to 40 wt% to less than or equal to 55 wt% of CaO, from greater than or equal to 45 wt% to less than or equal to 55 wt% of CaO, from greater than or equal to 50 wt% to less than or equal to 55 wt% of CaO, from greater than or equal to 30 wt% to less than or equal to 50 wt% of CaO, from greater than or equal to 35 wt% to less than or equal to 50 wt% of CaO, from greater than or equal to 40 wt% to less than or equal to 50 wt% of CaO, from greater than or equal to 45 wt% to less than or equal to 50 wt% of CaO, from greater than or equal to 30 wt% to less than or equal to 45 wt% of CaO, from greater than or equal to 35 wt% to less than or equal to 45 wt% of CaO, from greater than or equal to 40 wt% to less than or equal to 45 wt% of CaO, from greater than or equal to 30 wt% to less than or equal to 40 wt% of CaO, from greater than or equal to 35 wt% to less than or equal to 40 wt% of CaO, or from greater than or equal to 30 wt% to less than or equal to 35 wt% of CaO.
[0032] A combination of a relatively high P2O5 content relative to other bioactive glass compositions with a relatively high CaO content and a relatively low SiO2 is believed to improve the bioactivity of the bioactive glass compositions disclosed and described herein. P2O5 can also reduce the viscosity of the glass, which enhances formability, strain point, and Young's modulus. However, when too much P2O5 is added to the bioactive glass composition, the density and CTE of the bioactive glass composition increase. In embodiments, the bioactive glass composition comprises from greater than or equal to 8 wt% to less than or equal to 30 wt% P2O5, such as from greater than or equal to 10 wt% to less than or equal to 30 wt% P2O5, from greater than or equal to 15 wt% to less than or equal to 30 wt% P2O5, from greater than or equal to 20 wt% to less than or equal to 30 wt% P2O5, from greater than or equal to 25 wt% to less than or equal to 30 wt% P2O5, from greater than or equal to 8 wt% to less than or equal to 25 wt% P2O5, from greater than or equal to 10 wt% to less than or equal to 25 wt% P2O5, from greater than or equal to 15 wt% to less than or equal to 25 wt% P2O5, from greater than or equal to 20 wt% to less than or equal to 25 wt% P2O5, from greater than or equal to 8 wt% to less than or equal to 20 wt% P2O5, from greater than or equal to 10 wt% to less than or equal to 20 wt% P2O5, from greater than or equal to 15 wt% to less than or equal to 20 wt% P2O5, from greater than or equal to 8 wt% to less than or equal to 15 wt% P2O5, from greater than or equal to 10 wt% to less than or equal to 15 wt% P2O5, or from greater than or equal to 8 wt% to less than or equal to 10 wt% P2O5.
[0033] Including ZrO2 in a bioactive glass composition can also improve the bioactivity of the bioactive glass composition and can improve the stability of the bioactive glass composition. However, including too much ZrO2 can lead to unwanted crystallization of the bioactive glass composition or an increase in the viscosity of the bioactive glass composition. In an embodiment, the bioactive glass composition comprises from greater than or equal to 2 wt% to less than or equal to 15 wt% of ZrO2, such as from greater than or equal to 4 wt% to less than or equal to 15 wt% of ZrO2, from greater than or equal to 6 wt% to less than or equal to 15 wt% of ZrO2, from greater than or equal to 8 wt% to less than or equal to 15 wt% of ZrO2, from greater than or equal to 10 wt% to less than or equal to 15 wt% of ZrO2, from greater than or equal to 12 wt% to less than or equal to 15 wt% of ZrO2, from greater than or equal to 2 wt% to less than or equal to 12 wt% of ZrO2, from greater than or equal to 4 wt% to less than or equal to 12 wt% of ZrO2, from greater than or equal to 6 wt% to less than or equal to 12 wt% of ZrO2, from greater than or equal to 8 wt% to less than or equal to 12 wt% of ZrO2, from greater than or equal to 10 wt% to less than or equal to 12 wt% of ZrO2, from greater than or equal to 2 wt% to less than or equal to 10 wt% of ZrO2, from greater than or equal to 4 wt% to less than or equal to 10 wt% of ZrO2, from greater than or equal to 6 wt% to less than or equal to 10 wt% of ZrO2, from greater than or equal to 8 wt% to less than or equal to 10 wt% of ZrO2, from greater than or equal to 2 wt% to less than or equal to 8 wt% of ZrO2, from greater than or equal to 4 wt% to less than or equal to 8 wt% of ZrO2, from greater than or equal to 6 wt% to less than or equal to 8 wt% of ZrO2, from greater than or equal to 2 wt% to less than or equal to 6 wt% of ZrO2, from greater than or equal to 4 wt% to less than or equal to 6 wt% of ZrO2, from greater than or equal to 2 wt% to less than or equal to 4 wt% of ZrO2.
[0034] MgO reduces the viscosity of the glass, which enhances formability, strain point, and Young's modulus. However, when too much MgO is added to the bioactive glass composition, the density and CTE of the bioactive glass composition increase.In an embodiment, the bioactive glass composition comprises MgO in an amount less than or equal to 35 wt%, such as MgO in an amount greater than or equal to 0 wt% and less than or equal to 25 wt%, greater than or equal to 2 wt% and less than or equal to 25 wt%, greater than or equal to 5 wt% and less than or equal to 25 wt%, greater than or equal to 8 wt% and less than or equal to 25 wt%, greater than or equal to 10 wt% and less than or equal to 25 wt%, greater than or equal to 14 wt% and less than or equal to 25 wt%, greater than or equal to 18 wt% and less than or equal to 25 wt%, greater than or equal to 20 wt% and less than or equal to 25 wt%, greater than or equal to 0 wt% and less than or equal to 20 wt%, greater than or equal to 2 wt% and less than or equal to 20 wt%, greater than or equal to 5 wt% and less than or equal to 20 wt%, greater than or equal to 8 wt% and less than or equal to 20 wt%, greater than or equal to 10 wt% and less than or equal to 20 wt%, greater than or equal to 14 wt% and less than or equal to 20 wt%, greater than or equal to 18 wt% and less than or equal to 20 wt%, greater than or equal to 0 wt% and less than or equal to 18 wt%, greater than or equal to 2 wt% and less than or equal to 18 wt%, greater than or equal to 5 wt% and less than or equal to 18 wt%, greater than or equal to 8 wt% and less than or equal to 18 wt%, greater than or equal to 10 wt% and less than or equal to 18 wt%, greater than or equal to 14 wt% and less than or equal to 18 wt%, greater than or equal to 0 wt% and less than or equal to 14 wt%, greater than or equal to 2 wt% and less than or equal to 14 wt%, greater than or equal to 5 wt% and less than or equal to 14 wt%, greater than or equal to 8 wt% and less than or equal to 14 wt%, greater than or equal to 10 wt% and less than or equal to 14 wt%, greater than or equal to 0 wt% and less than or equal to 10 wt%, greater than or equal to 2 wt% and less than or equal to 10 wt%, greater than or equal to 5 wt% and less than or equal to 10 wt%, greater than or equal to 8 wt% and less than or equal to 10 wt%, greater than or equal to 0 wt% and less than or equal to 8 wt%, greater than or equal to 2 wt% and less than or equal to 8 wt%, greater than or equal to 5 wt% and less than or equal to 8 wt%, greater than or equal to 0 wt% and less than or equal to 5 wt%, greater than or equal to 2 wt% and less than or equal to 5 wt%, or greater than or equal to 0 wt% and less than or equal to 2 wt%.
[0035] SrO reduces the viscosity of the glass, which enhances formability, strain point, and Young's modulus. However, when too much SrO is added to the bioactive glass composition, the density and CTE of the bioactive glass composition increase. In embodiments, the bioactive glass composition comprises SrO in an amount less than or equal to 10 wt%, such as SrO in an amount greater than or equal to 0 wt% and less than or equal to 10 wt%, SrO in an amount greater than or equal to 2 wt% and less than or equal to 10 wt%, SrO in an amount greater than or equal to 4 wt% and less than or equal to 10 wt%, SrO in an amount greater than or equal to 6 wt% and less than or equal to 10 wt%, SrO in an amount greater than or equal to 8 wt% and less than or equal to 10 wt%, SrO in an amount greater than or equal to 0 wt% and less than or equal to 8 wt%, SrO in an amount greater than or equal to 2 wt% and less than or equal to 8 wt%, SrO in an amount greater than or equal to 4 wt% and less than or equal to 8 wt%, SrO in an amount greater than or equal to 6 wt% and less than or equal to 8 wt%, SrO in an amount greater than or equal to 0 wt% and less than or equal to 6 wt%, SrO in an amount greater than or equal to 2 wt% and less than or equal to 6 wt%, SrO in an amount greater than or equal to 4 wt% and less than or equal to 6 wt%, SrO in an amount greater than or equal to 0 wt% and less than or equal to 4 wt%, SrO in an amount greater than or equal to 2 wt% and less than or equal to 4 wt%, or SrO in an amount greater than or equal to 0 wt% and less than or equal to 2 wt%.
[0036] ZnO reduces the viscosity of the glass, which enhances formability, strain point, and Young's modulus. However, when too much ZnO is added to the bioactive glass composition, the density and CTE of the bioactive glass composition increase. In embodiments, the bioactive glass composition comprises ZnO in an amount less than or equal to 10 wt%, such as ZnO in an amount greater than or equal to 0 wt% and less than or equal to 10 wt%, ZnO in an amount greater than or equal to 2 wt% and less than or equal to 10 wt%, ZnO in an amount greater than or equal to 4 wt% and less than or equal to 10 wt%, ZnO in an amount greater than or equal to 6 wt% and less than or equal to 10 wt%, ZnO in an amount greater than or equal to 8 wt% and less than or equal to 10 wt%, ZnO in an amount greater than or equal to 0 wt% and less than or equal to 8 wt%, ZnO in an amount greater than or equal to 2 wt% and less than or equal to 8 wt%, ZnO in an amount greater than or equal to 4 wt% and less than or equal to 8 wt%, ZnO in an amount greater than or equal to 6 wt% and less than or equal to 8 wt%, ZnO in an amount greater than or equal to 0 wt% and less than or equal to 6 wt%, ZnO in an amount greater than or equal to 2 wt% and less than or equal to 6 wt%, ZnO in an amount greater than or equal to 4 wt% and less than or equal to 6 wt%, ZnO in an amount greater than or equal to 0 wt% and less than or equal to 4 wt%, ZnO in an amount greater than or equal to 2 wt% and less than or equal to 4 wt%, or ZnO in an amount greater than or equal to 0 wt% and less than or equal to 2 wt%.
[0037] According to an embodiment, the bioactive glass composition may further comprise alkali metals such as Li2O, Na2O, and K2O. However, the alkali metal content in the bioactive glass composition should be relatively low to allow for improved water durability in an aqueous solution and faster conversion to apatite in saliva. Thus, some embodiments of the bioactive glass compositions disclosed and described herein do not include alkali metals, and other embodiments include a small amount of alkali metals.
[0038] In an embodiment, the bioactive glass composition comprises less than or equal to 10 wt% of Li2O, such as greater than or equal to 0 wt% and less than or equal to 10 wt% of Li2O, greater than or equal to 2 wt% and less than or equal to 10 wt% of Li2O, greater than or equal to 4 wt% and less than or equal to 10 wt% of Li2O, greater than or equal to 6 wt% and less than or equal to 10 wt% of Li2O, greater than or equal to 8 wt% and less than or equal to 10 wt% of Li2O, greater than or equal to 0 wt% and less than or equal to 8 wt% of Li2O, greater than or equal to 2 wt% and less than or equal to 8 wt% of Li2O, greater than or equal to 4 wt% and less than or equal to 8 wt% of Li2O, greater than or equal to 6 wt% and less than or equal to 8 wt% of Li2O, greater than or equal to 0 wt% and less than or equal to 6 wt% of Li2O, greater than or equal to 2 wt% and less than or equal to 6 wt% of Li2O, greater than or equal to 4 wt% and less than or equal to 6 wt% of Li2O, greater than or equal to 0 wt% and less than or equal to 4 wt% of Li2O, greater than or equal to 2 wt% and less than or equal to 4 wt% of Li2O, or greater than or equal to 0 wt% and less than or equal to 2 wt% of Li2O.
[0039] In an embodiment, the bioactive glass composition comprises up to 10 wt% of Na2O, such as from 0 wt% to 10 wt% of Na2O, from 2 wt% to 10 wt% of Na2O, from 4 wt% to 10 wt% of Na2O, from 6 wt% to 10 wt% of Na2O, from 8 wt% to 10 wt% of Na2O, from 0 wt% to 8 wt% of Na2O, from 2 wt% to 8 wt% of Na2O, from 4 wt% to 8 wt% of Na2O, from 6 wt% to 8 wt% of Na2O, from 0 wt% to 6 wt% of Na2O, from 2 wt% to 6 wt% of Na2O, from 4 wt% to 6 wt% of Na2O, from 0 wt% to 4 wt% of Na2O, from 2 wt% to 4 wt% of Na2O, or from 0 wt% to 2 wt% of Na2O.
[0040] In an embodiment, the bioactive glass composition comprises up to 10 wt% of K2O, such as from 0 wt% to 10 wt% of K2O, from 2 wt% to 10 wt% of K2O, from 4 wt% to 10 wt% of K2O, from 6 wt% to 10 wt% of K2O, from 8 wt% to 10 wt% of K2O, from 0 wt% to 8 wt% of K2O, from 2 wt% to 8 wt% of K2O, from 4 wt% to 8 wt% of K2O, from 6 wt% to 8 wt% of K2O, from 0 wt% to 6 wt% of K2O, from 2 wt% to 6 wt% of K2O, from 4 wt% to 6 wt% of K2O, from 0 wt% to 4 wt% of K2O, from 2 wt% to 4 wt% of K2O, or from 0 wt% to 2 wt% of K2O.
[0041] Similar to SiO2, Al2O3 can act as a glass network former. Al2O3 can increase the viscosity of the bioactive glass composition due to its tetrahedral coordination in the glass melt formed from a properly designed bioactive glass composition, so that when the amount of Al2O3 is too high, the formability of the bioactive glass composition decreases. In the examples, the bioactive glass composition contains less than or equal to 5 wt% of Al2O3, such as from greater than or equal to 0 wt% and less than or equal to 5 wt% of Al2O3, from greater than or equal to 1 wt% and less than or equal to 5 wt% of Al2O3, from greater than or equal to 2 wt% and less than or equal to 5 wt% of Al2O3, from greater than or equal to 3 wt% and less than or equal to 5 wt% of Al2O3, from greater than or equal to 4 wt% and less than or equal to 5 wt% of Al2O3, from greater than or equal to 0 wt% and less than or equal to 4 wt% of Al2O3, from greater than or equal to 1 wt% and less than or equal to 4 wt% of Al2O3, from greater than or equal to 2 wt% and less than or equal to 4 wt% of Al2O3, from greater than or equal to 3 wt% and less than or equal to 4 wt% of Al2O3, from greater than or equal to 0 wt% and less than or equal to 3 wt% of Al2O3, from greater than or equal to 1 wt% and less than or equal to 3 wt% of Al2O3, from greater than or equal to 2 wt% and less than or equal to 3 wt% of Al2O3, from greater than or equal to 0 wt% and less than or equal to 2 wt% of Al2O3, from greater than or equal to 1 wt% and less than or equal to 2 wt% of Al2O3, or from greater than or equal to 0 wt% and less than or equal to 1 wt% of Al2O3.
[0042] In the examples, the bioactive glass composition can include less than 5 wt% of F - , such as from greater than or equal to 0 wt% and less than or equal to 5 wt% of F - , from greater than or equal to 1 wt% and less than or equal to 5 wt% of F - , from greater than or equal to 2 wt% and less than or equal to 5 wt% of F - , from greater than or equal to 3 wt% and less than or equal to 5 wt% of F - , from greater than or equal to 4 wt% and less than or equal to 5 wt% of F - , from greater than or equal to 0 wt% and less than or equal to 4 wt% of F - , from greater than or equal to 1 wt% and less than or equal to 4 wt% of F - , from greater than or equal to 2 wt% and less than or equal to 4 wt% of F - , from greater than or equal to 3 wt% and less than or equal to 4 wt% of F - , from greater than or equal to 0 wt% and less than or equal to 3 wt% of F - , from greater than or equal to 1 wt% and less than or equal to 3 wt% of F -, F of greater than or equal to 2% by weight and less than or equal to 3% by weight - , F of greater than or equal to 0% by weight and less than or equal to 2% by weight - , F of greater than or equal to 1% by weight and less than or equal to 2% by weight - , or F of greater than or equal to 0% by weight and less than or equal to 1% by weight - .
[0043] In one or more embodiments, the bioactive glass composition comprises SiO2 of greater than or equal to 20.0% by weight and less than or equal to 39.5% by weight, MgO of greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight, CaO of greater than or equal to 32.5% by weight and less than or equal to 47.0% by weight, SrO of greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight, ZnO of greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight, P2O5 of greater than or equal to 9.5% by weight and less than or equal to 24.5% by weight, and ZrO2 of greater than or equal to 4.0% by weight and less than or equal to 10.0% by weight.
[0044] In one or more embodiments, the bioactive glass composition comprises SiO2 of greater than or equal to 20.5% by weight and less than or equal to 37.5% by weight, MgO of greater than or equal to 0.0% by weight and less than or equal to 4.5% by weight, CaO of greater than or equal to 32.5% by weight and less than or equal to 42.5% by weight, P2O5 of greater than or equal to 11.5% by weight and less than or equal to 24.5% by weight, and ZrO2 of greater than or equal to 4.0% by weight and less than or equal to 10.0% by weight.
[0045] In one or more embodiments, the bioactive glass composition comprises SiO2 of greater than or equal to 25% by weight and less than or equal to 35% by weight, MgO of greater than or equal to 2.0% by weight and less than or equal to 6.0% by weight, CaO of greater than or equal to 35.0% by weight and less than or equal to 45.0% by weight, P2O5 of greater than or equal to 15.0% by weight and less than or equal to 25.0% by weight, and ZrO2 of greater than or equal to 2.0% by weight and less than or equal to 6.0% by weight.
[0046] In an embodiment, the melting point of the bioactive glass composition is less than or equal to 1400 °C, such as less than or equal to 1300 °C, less than or equal to 1200 °C, or less than or equal to 1100 °C. In one or more embodiments, the melting point of the bioactive glass is greater than or equal to 800 °C and less than or equal to 1400 °C, such as greater than or equal to 900 °C and less than or equal to 1400 °C, greater than or equal to 1000 °C and less than or equal to 1400 °C, greater than or equal to 1100 °C and less than or equal to 1400 °C, greater than or equal to 1200 °C and less than or equal to 1400 °C, greater than or equal to 1300 °C and less than or equal to 1400 °C, greater than or equal to 800 °C and less than or equal to 1300 °C, greater than or equal to 900 °C and less than or equal to 1300 °C, greater than or equal to 1000 °C and less than or equal to 1300 °C, greater than or equal to 1100 °C and less than or equal to 1300 °C, greater than or equal to 1200 °C and less than or equal to 1300 °C, greater than or equal to 800 °C and less than or equal to 1200 °C, greater than or equal to 900 °C and less than or equal to 1200 °C, greater than or equal to 1000 °C and less than or equal to 1200 °C, greater than or equal to 1100 °C and less than or equal to 1200 °C, greater than or equal to 800 °C and less than or equal to 1100 °C, greater than or equal to 900 °C and less than or equal to 1100 °C, greater than or equal to 1000 °C and less than or equal to 1100 °C, greater than or equal to 800 °C and less than or equal to 1000 °C, greater than or equal to 900 °C and less than or equal to 1000 °C, or greater than or equal to 800 °C and less than or equal to 900 °C. These relatively low melting points enable the bioactive glass composition to be melted in a small commercial boiler.
[0047] As will be described in more detail below, the bioactive glass composition according to the embodiments disclosed and described herein is durable in an aqueous solution. Durability is measured by the weight loss of the bioactive glass composition after exposure to deionized water for a period of time. In an embodiment, the weight loss of the bioactive glass composition after 7 days of exposure to deionized water is less than or equal to 5 wt%, such as less than or equal to 4 wt% after 7 days of exposure to deionized water, less than or equal to 3 wt% after 7 days of exposure to deionized water, less than or equal to 2 wt% after 7 days of exposure to deionized water, or less than or equal to 1 wt% after 7 days of exposure to deionized water. In some embodiments, the bioactive glass composition does not lose a measurable amount of weight after 7 days in deionized water (about 0% weight loss). The bioactive glass composition can be used in aqueous dentifrice formulations due to the above durability in an aqueous solution, while glass compositions conventionally used in dentifrice formulations cannot.
[0048] In addition to durability in an aqueous solution, the bioactive glass compositions according to the embodiments disclosed and described herein also have durability in saliva. Durability is measured by the weight loss of the bioactive glass composition after exposure to artificial saliva manufactured by Modus Laboratories for a period of time. In an embodiment, the weight loss of the bioactive glass composition disclosed and described herein after exposure to artificial saliva for 7 days is less than or equal to 9 wt%, such as less than or equal to 8 wt% after exposure to artificial saliva for 7 days, less than or equal to 7 wt% after exposure to artificial saliva for 7 days, less than or equal to 6 wt% after exposure to artificial saliva for 7 days, less than or equal to 5 wt% after exposure to artificial saliva for 7 days, less than or equal to 4 wt% after exposure to artificial saliva for 7 days, less than or equal to 2 wt% after exposure to artificial saliva for 7 days, or less than or equal to 1 wt% after exposure to artificial saliva for 7 days. In some embodiments, the bioactive glass composition does not lose a measurable amount of weight (approximately 0% weight loss) after 7 days in artificial saliva.
[0049] The bioactive glass compositions as disclosed and described herein also have higher bioactivity than glass compositions conventionally used in dentifrice formulations. In an embodiment, the formation of dispersed crystals occurs within 2 days of immersion in artificial saliva. Within 4 days of immersion in artificial saliva, the entire surface of the glass powder is covered by a well-developed crystalline phase. The crystalline phase observed is hydroxyapatite, which indicates good bioactivity. For comparison, a conventional glass composition for a dentifrice formulation does not show apatite formation after 7 days of immersion in artificial saliva.
[0050] The bioactive glass compositions according to the embodiments disclosed and described herein can be used as an active ingredient in a dentifrice formulation. The dentifrice formulation according to the embodiments disclosed and described herein will now be described.
[0051] The dentifrice formulation of the embodiment includes the bioactive glass composition disclosed and described herein, a solvent, and one or more humectants. In an embodiment, the solvent is water and it will be referred to as an aqueous dentifrice formulation. In other embodiments, the solvent is a non-aqueous solvent, such as glycerol, and it will be referred to as a non-aqueous dentifrice formulation. In an embodiment, the dentifrice formulation contains greater than or equal to 1 wt% and less than or equal to 20 wt% of the bioactive glass composition, greater than or equal to 10 wt% and less than or equal to 80 wt% of a surfactant (aqueous or non-aqueous), and greater than or equal to 2 wt% and less than or equal to 50 wt% of a humectant.
[0052] First, and according to an embodiment, the bioactive glass composition of the embodiment can be formed into a fine powder or microbeads to be added to a dentifrice formulation. This can be accomplished by any suitable method, such as, for example, ball milling, jet milling, etc. In an embodiment, the bioactive glass composition can be formed into a powder or microbeads having a particle size distribution D99 less than or equal to 10 μm, such as less than or equal to 9 μm, less than or equal to 8 μm, less than or equal to 7 μm, less than or equal to 6 μm, less than or equal to 5 μm, less than or equal to 4 μm, less than or equal to 3 μm, less than or equal to 2 μm, or less than or equal to 1 μm. In an embodiment, the D99 particle size distribution is greater than or equal to 1 μm and less than or equal to 10 μm, such as greater than or equal to 2 μm and less than or equal to 10 μm, greater than or equal to 4 μm and less than or equal to 10 μm, greater than or equal to 6 μm and less than or equal to 10 μm, greater than or equal to 8 μm and less than or equal to 10 μm, greater than or equal to 1 μm and less than or equal to 8 μm, greater than or equal to 2 μm and less than or equal to 8 μm, greater than or equal to 4 μm and less than or equal to 8 μm, greater than or equal to 6 μm and less than or equal to 8 μm, greater than or equal to 1 μm and less than or equal to 6 μm, greater than or equal to 2 μm and less than or equal to 6 μm, greater than or equal to 4 μm and less than or equal to 6 μm, greater than or equal to 1 μm and less than or equal to 4 μm, greater than or equal to 2 μm and less than or equal to 4 μm, or greater than or equal to 1 μm and less than or equal to 2 μm.
[0053] The dentifrice formulations of the embodiments disclosed and described herein comprise a bioactive glass composition as disclosed and described herein in an amount greater than or equal to 1 wt% and less than or equal to 20 wt%, such as greater than or equal to 2 wt% and less than or equal to 20 wt%, greater than or equal to 5 wt% and less than or equal to 20 wt%, greater than or equal to 8 wt% and less than or equal to 20 wt%, greater than or equal to 10 wt% and less than or equal to 20 wt%, greater than or equal to 12 wt% and less than or equal to 20 wt%, greater than or equal to 15 wt% and less than or equal to 20 wt%, greater than or equal to 18 wt% and less than or equal to 20 wt%, greater than or equal to 1 wt% and less than or equal to 18 wt%, greater than or equal to 2 wt% and less than or equal to 18 wt%, greater than or equal to 5 wt% and less than or equal to 18 wt%, greater than or equal to 8 wt% and less than or equal to 18 wt%, greater than or equal to 10 wt% and less than or equal to 18 wt%, greater than or equal to 12 wt% and less than or equal to 18 wt%, greater than or equal to 15 wt% and less than or equal to 18 wt%, greater than or equal to 1 wt% and less than or equal to 15 wt%, greater than or equal to 2 wt% and less than or equal to 15 wt%, greater than or equal to 5 wt% and less than or equal to 15 wt%, greater than or equal to 8 wt% and less than or equal to 15 wt%, greater than or equal to 10 wt% and less than or equal to 15 wt%, greater than or equal to 12 wt% and less than or equal to 15 wt%, greater than or equal to 1 wt% and less than or equal to 12 wt%, greater than or equal to 2 wt% and less than or equal to 12 wt%, greater than or equal to 5 wt% and less than or equal to 12 wt%, greater than or equal to 8 wt% and less than or equal to 12 wt%, greater than or equal to 10 wt% and less than or equal to 12 wt%, greater than or equal to 1 wt% and less than or equal to 10 wt%, greater than or equal to 2 wt% and less than or equal to 10 wt%, greater than or equal to 5 wt% and less than or equal to 10 wt%, greater than or equal to 8 wt% and less than or equal to 10 wt%, greater than or equal to 1 wt% and less than or equal to 8 wt%, greater than or equal to 2 wt% and less than or equal to 8 wt%, greater than or equal to 5 wt% and less than or equal to 8 wt%, greater than or equal to 1 wt% and less than or equal to 5 wt%, greater than or equal to 2 wt% and less than or equal to 5 wt%, or greater than or equal to 1 wt% and less than or equal to 2 wt%. If the dentifrice formulation contains too much bioactive glass, then the composition will not have a consistency suitable for application. However, if the dentifrice formulation does not contain enough bioactive glass, then its performance will not be good.
[0054] The dentifrice formulation according to the embodiment comprises a solvent (aqueous or non-aqueous) in an amount greater than or equal to 10% by weight and less than or equal to 80% by weight, such as greater than or equal to 20% by weight and less than or equal to 80% by weight, greater than or equal to 30% by weight and less than or equal to 80% by weight, greater than or equal to 40% by weight and less than or equal to 80% by weight, greater than or equal to 50% by weight and less than or equal to 80% by weight, greater than or equal to 60% by weight and less than or equal to 80% by weight, greater than or equal to 70% by weight and less than or equal to 80% by weight, greater than or equal to 10% by weight and less than or equal to 70% by weight, greater than or equal to 20% by weight and less than or equal to 70% by weight, greater than or equal to 30% by weight and less than or equal to 70% by weight, greater than or equal to 40% by weight and less than or equal to 70% by weight, greater than or equal to 50% by weight and less than or equal to 70% by weight, greater than or equal to 60% by weight and less than or equal to 70% by weight, greater than or equal to 10% by weight and less than or equal to 60% by weight, greater than or equal to 20% by weight and less than or equal to 60% by weight, greater than or equal to 30% by weight and less than or equal to 60% by weight, greater than or equal to 40% by weight and less than or equal to 60% by weight, greater than or equal to 50% by weight and less than or equal to 60% by weight, greater than or equal to 10% by weight and less than or equal to 50% by weight, greater than or equal to 20% by weight and less than or equal to 50% by weight, greater than or equal to 30% by weight and less than or equal to 50% by weight, greater than or equal to 40% by weight and less than or equal to 50% by weight, greater than or equal to 10% by weight and less than or equal to 40% by weight, greater than or equal to 20% by weight and less than or equal to 40% by weight, greater than or equal to 30% by weight and less than or equal to 40% by weight, greater than or equal to 10% by weight and less than or equal to 30% by weight, greater than or equal to 20% by weight and less than or equal to 30% by weight, or greater than or equal to 10% by weight and less than or equal to 20% by weight.
[0055] In an embodiment, the dentifrice formulation comprises one or more humectants. Humectants according to an embodiment include short-chain polyols. By way of example, humectants according to an embodiment preferably include short-chain polyols selected from the group consisting of glycerin, sorbitol, propylene glycol, and polyethylene glycol. The dentifrice formulation according to an embodiment includes from greater than or equal to 2 wt% to less than or equal to 50 wt% of a humectant, such as from greater than or equal to 5 wt% to less than or equal to 50 wt%, from greater than or equal to 10 wt% to less than or equal to 50 wt%, from greater than or equal to 20 wt% to less than or equal to 50 wt%, from greater than or equal to 30 wt% to less than or equal to 50 wt%, from greater than or equal to 40 wt% to less than or equal to 50 wt%, from greater than or equal to 2 wt% to less than or equal to 40 wt%, from greater than or equal to 5 wt% to less than or equal to 40 wt%, from greater than or equal to 10 wt% to less than or equal to 40 wt%, from greater than or equal to 20 wt% to less than or equal to 40 wt%, from greater than or equal to 30 wt% to less than or equal to 40 wt%, from greater than or equal to 2 wt% to less than or equal to 30 wt%, from greater than or equal to 5 wt% to less than or equal to 30 wt%, from greater than or equal to 10 wt% to less than or equal to 30 wt%, from greater than or equal to 20 wt% to less than or equal to 30 wt%, from greater than or equal to 2 wt% to less than or equal to 20 wt%, from greater than or equal to 5 wt% to less than or equal to 20 wt%, from greater than or equal to 10 wt% to less than or equal to 20 wt%, from greater than or equal to 2 wt% to less than or equal to 10 wt%, from greater than or equal to 5 wt% to less than or equal to 10 wt%, or from greater than or equal to 2 wt% to less than or equal to 5 wt%. The humectant prevents moisture loss and provides a creamy texture to the dentifrice formulation. Too little humectant added will result in a dry and unpleasant texture. Too much humectant added can result in an overly wet dentifrice formulation.
[0056] In one or more embodiments, the dentifrice formulation includes other additives conventionally used in dentifrice formulations. These additives can include surfactants, desensitizing agents (including potassium salts), fluoride sources, whitening agents, tartar control agents, antibacterial agents, abrasives (including silica), binders and thickeners, detergents, adhesives, foam regulators, pH regulators, flavoring agents, sweeteners, flavorings, colorants, preservatives, combinations of the foregoing, and the like. One or more of these additives can be included in the dentifrice formulation.
[0057] In an embodiment, the dentifrice formulation comprises a bioactive glass composition in an amount greater than or equal to 1 wt% and less than or equal to 20 wt%, a surfactant (aqueous or non-aqueous) in an amount greater than or equal to 10 wt% and less than or equal to 80 wt%, a humectant in an amount greater than or equal to 2 wt% and less than or equal to 50 wt%, fluoride ions in an amount greater than or equal to 0.01 wt% and less than or equal to 1.00 wt%, a flavoring agent in an amount greater than or equal to 0.05 wt% and less than or equal to 5.00 wt%, a surfactant in an amount greater than or equal to 0.1 wt% and less than or equal to 5.0 wt%, a sweetening agent in an amount greater than or equal to 0.1 wt% and less than or equal to 5.0 wt%, a whitening agent in an amount greater than or equal to 0.1 wt% and less than or equal to 2.0 wt%, and an abrasive in an amount greater than or equal to 0.1 wt% and less than or equal to 20.0 wt%.
[0058] In one or more embodiments, the dentifrice formulation comprises a fluoride ion source, such as an alkali metal fluoride, a fluorinated amine, stannous fluoride. In an embodiment, the fluoride ion source is selected from the group consisting of sodium fluoride, potassium fluoride, ammonium fluoride, monofluorophosphate, and mixtures of the foregoing. The dentifrice formulation comprises an amount of the fluoride ion source such that the amount of fluoride ions in the dentifrice formulation is within the desired range. According to an embodiment, the dentifrice formulation comprises fluoride ions in an amount greater than or equal to 0.01 wt% and less than or equal to 1.00 wt%, such as greater than or equal to 0.05 wt% and less than or equal to 1.00 wt%, greater than or equal to 0.10 wt% and less than or equal to 1.00 wt%, greater than or equal to 0.25 wt% and less than or equal to 1.00 wt%, greater than or equal to 0.50 wt% and less than or equal to 1.00 wt%, greater than or equal to 0.75 wt% and less than or equal to 1.00 wt%, greater than or equal to 0.01 wt% and less than or equal to 0.75 wt%, greater than or equal to 0.05 wt% and less than or equal to 0.75 wt%, greater than or equal to 0.10 wt% and less than or equal to 0.75 wt%, greater than or equal to 0.25 wt% and less than or equal to 0.75 wt%, greater than or equal to 0.50 wt% and less than or equal to 0.75 wt%, greater than or equal to 0.01 wt% and less than or equal to 0.50 wt%, greater than or equal to 0.05 wt% and less than or equal to 0.50 wt%, greater than or equal to 0.10 wt% and less than or equal to 0.50 wt%, greater than or equal to 0.25 wt% and less than or equal to 0.50 wt%, greater than or equal to 0.01 wt% and less than or equal to 0.25 wt%, greater than or equal to 0.05 wt% and less than or equal to 0.25 wt%, greater than or equal to 0.10 wt% and less than or equal to 0.25 wt%, greater than or equal to 0.01 wt% and less than or equal to 0.10 wt%, greater than or equal to 0.05 wt% and less than or equal to 0.10 wt%, or greater than or equal to 0.01 wt% and less than or equal to 0.05 wt%.
[0059] Examples of dentifrice formulations contain a flavoring agent in an amount greater than or equal to 0.05 wt% and less than or equal to 5.00 wt%, such as a flavoring agent in an amount greater than or equal to 0.50 wt% and less than or equal to 5.00 wt%, greater than or equal to 1.00 wt% and less than or equal to 5.00 wt%, greater than or equal to 1.50 wt% and less than or equal to 5.00 wt%, greater than or equal to 2.00 wt% and less than or equal to 5.00 wt%, greater than or equal to 2.50 wt% and less than or equal to 5.00 wt%, greater than or equal to 3.00 wt% and less than or equal to 5.00 wt%, greater than or equal to 3.50 wt% and less than or equal to 5.00 wt%, greater than or equal to 4.00 wt% and less than or equal to 5.00 wt%, greater than or equal to 4.50 wt% and less than or equal to 5.00 wt%, greater than or equal to 0.05 wt% and less than or equal to 4.50 wt% of a flavoring agent, greater than or equal to 0.50 wt% and less than or equal to 4.50 wt%, greater than or equal to 1.00 wt% and less than or equal to 4.50 wt%, greater than or equal to 1.50 wt% and less than or equal to 4.50 wt%, greater than or equal to 2.00 wt% and less than or equal to 4.50 wt%, greater than or equal to 2.50 wt% and less than or equal to 4.50 wt%, greater than or equal to 3.00 wt% and less than or equal to 4.50 wt%, greater than or equal to 3.50 wt% and less than or equal to 4.50 wt%, greater than or equal to 0.05 wt% and less than or equal to 4.00 wt% of a flavoring agent, greater than or equal to 0.50 wt% and less than or equal to 4.00 wt%, greater than or equal to 1.00 wt% and less than or equal to 4.00 wt%, greater than or equal to 1.50 wt% and less than or equal to 4.00 wt%, greater than or equal to 2.00 wt% and less than or equal to 4.00 wt%, greater than or equal to 2.50 wt% and less than or equal to 4.00 wt%, greater than or equal to 3.00 wt% and less than or equal to 4.00 wt%, greater than or equal to 3.50 wt% and less than or equal to 4.00 wt%, greater than or equal to 0.05 wt% and less than or equal to 3.50 wt% of a flavoring agent, greater than or equal to 0.50 wt% and less than or equal to 3.50 wt%, greater than or equal to 1.00 wt% and less than or equal to 3.50 wt%, greater than or equal to 1.50 wt% and less than or equal to 3.50 wt%, greater than or equal to 2.00 wt% and less than or equal to 3.50 wt%, greater than or equal to 2.50 wt% and less than or equal to 3.50 wt%, greater than or equal to 3.00 wt% and less than or equal to 3.50 wt%, greater than or equal to 0.05 wt% and less than or equal to 3.00 wt% of a flavoring agent, greater than or equal to 0.50 wt% and less than or equal to 3.00 wt%, greater than or equal to 1.00 wt% and less than or equal to 3.00 wt%, greater than or equal to 1.Flavoring agents in an amount of 50% by weight and less than or equal to 3.00% by weight, greater than or equal to 2.00% by weight and less than or equal to 3.00% by weight, greater than or equal to 2.50% by weight and less than or equal to 3.00% by weight, greater than or equal to 0.05% by weight and less than or equal to 2.50% by weight, greater than or equal to 0.50% by weight and less than or equal to 2.50% by weight, greater than or equal to 1.00% by weight and less than or equal to 2.50% by weight, greater than or equal to 1.50% by weight and less than or equal to 2.50% by weight, greater than or equal to 2.00% by weight and less than or equal to 2.50% by weight, greater than or equal to 0.05% by weight and less than or equal to 2.00% by weight, greater than or equal to 0.50% by weight and less than or equal to 2.00% by weight, greater than or equal to 1.00% by weight and less than or equal to 2.00% by weight, greater than or equal to 1.50% by weight and less than or equal to 2.00% by weight, greater than or equal to 0.05% by weight and less than or equal to 1.50% by weight, greater than or equal to 0.50% by weight and less than or equal to 1.50% by weight, greater than or equal to 1.00% by weight and less than or equal to 1.50% by weight, greater than or equal to 0.05% by weight and less than or equal to 1.00% by weight, greater than or equal to 0.50% by weight and less than or equal to 1.00% by weight, or greater than or equal to 0.05% by weight and less than or equal to 0.50% by weight.
[0060] In an embodiment, the dentifrice formulation comprises a surfactant selected from sodium lauryl sulfate, poloxamer (such as ethylene oxide / propylene oxide copolymer), and mixtures thereof. The dentifrice formulation according to the embodiment comprises from greater than or equal to 0.1 wt% to less than or equal to 5.0 wt% of the surfactant, such as from greater than or equal to 0.5 wt% to less than or equal to 5.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 5.0 wt%, from greater than or equal to 2.0 wt% to less than or equal to 5.0 wt%, from greater than or equal to 3.0 wt% to less than or equal to 5.0 wt%, from greater than or equal to 4.0 wt% to less than or equal to 5.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 4.0 wt%, from greater than or equal to 0.5 wt% to less than or equal to 4.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 4.0 wt%, from greater than or equal to 2.0 wt% to less than or equal to 4.0 wt%, from greater than or equal to 3.0 wt% to less than or equal to 4.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 3.0 wt%, from greater than or equal to 0.5 wt% to less than or equal to 3.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 3.0 wt%, from greater than or equal to 2.0 wt% to less than or equal to 3.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 2.0 wt%, from greater than or equal to 0.5 wt% to less than or equal to 2.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 2.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 1.0 wt%, from greater than or equal to 0.5 wt% to less than or equal to 1.0 wt%, or from greater than or equal to 0.1 wt% to less than or equal to 0.5 wt%.
[0061] According to an embodiment, the dentifrice formulation comprises a sweetening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 5.0% by weight, such as greater than or equal to 0.5% by weight and less than or equal to 5.0% by weight, greater than or equal to 1.0% by weight and less than or equal to 5.0% by weight, greater than or equal to 2.0% by weight and less than or equal to 5.0% by weight, greater than or equal to 3.0% by weight and less than or equal to 5.0% by weight, greater than or equal to 4.0% by weight and less than or equal to 5.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 4.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 4.0% by weight, greater than or equal to 1.0% by weight and less than or equal to 4.0% by weight, greater than or equal to 2.0% by weight and less than or equal to 4.0% by weight, greater than or equal to 3.0% by weight and less than or equal to 4.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 3.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 3.0% by weight, greater than or equal to 1.0% by weight and less than or equal to 3.0% by weight, greater than or equal to 2.0% by weight and less than or equal to 3.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 2.0% by weight, greater than or equal to 1.0% by weight and less than or equal to 2.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 1.0% by weight, or greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight.
[0062] The dentifrice formulation according to an embodiment comprises a whitening agent, such as a whitening agent selected from the group consisting of titanium dioxide, hydrogen peroxide, sodium tripolyphosphate, and mixtures of the foregoing. The dentifrice formulation according to an embodiment comprises a whitening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight, such as greater than or equal to 0.5% by weight and less than or equal to 2.0% by weight, greater than or equal to 1.0% by weight and less than or equal to 2.0% by weight, greater than or equal to 1.5% by weight and less than or equal to 2.0% by weight, greater than or equal to 0.1% by weight and less than or equal to 1.5% by weight, greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight, greater than or equal to 1.0% by weight and less than or equal to 1.5% by weight, greater than or equal to 0.1% by weight and less than or equal to 1.0% by weight, greater than or equal to 0.5% by weight and less than or equal to 1.0% by weight, or greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight.
[0063] In an embodiment, the dentifrice formulation contains an abrasive, such as an abrasive selected from the group consisting of silica, zinc orthophosphate, sodium bicarbonate, alumina, calcium carbonate, calcium pyrophosphate, and mixtures of the foregoing. The dentifrice formulation of the embodiment contains from greater than or equal to 0.1 wt% to less than or equal to 20.0 wt% of an abrasive, such as from greater than or equal to 1.0 wt% to less than or equal to 20.0 wt%, from greater than or equal to 5.0 wt% to less than or equal to 20.0 wt%, from greater than or equal to 10.0 wt% to less than or equal to 20.0 wt%, from greater than or equal to 15.0 wt% to less than or equal to 20.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 15.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 15.0 wt%, from greater than or equal to 5.0 wt% to less than or equal to 15.0 wt%, from greater than or equal to 10.0 wt% to less than or equal to 15.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 10.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 10.0 wt%, from greater than or equal to 5.0 wt% to less than or equal to 10.0 wt%, from greater than or equal to 0.1 wt% to less than or equal to 5.0 wt%, from greater than or equal to 1.0 wt% to less than or equal to 5.0 wt%, or from greater than or equal to 0.1 wt% to less than or equal to 1.0 wt%.
[0064] In some embodiments, the dentifrice composition comprises a tartar control (anti-calculus) agent. These agents include phosphates and polyphosphates such as sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium tripolyphosphate, sodium metaphosphate, sodium hexametaphosphate, and mixtures of the foregoing. Embodiments of the dentifrice formulation comprise from greater than or equal to 0.05 wt% to less than or equal to 0.50 wt% of the tartar control agent, such as from greater than or equal to 0.10 wt% to less than or equal to 0.50 wt%, from greater than or equal to 0.20 wt% to less than or equal to 0.50 wt%, from greater than or equal to 0.25 wt% to less than or equal to 0.50 wt%, from greater than or equal to 0.30 wt% to less than or equal to 0.50 wt%, from greater than or equal to 0.40 wt% to less than or equal to 0.50 wt%, from greater than or equal to 0.05 wt% to less than or equal to 0.40 wt%, from greater than or equal to 0.10 wt% to less than or equal to 0.40 wt%, from greater than or equal to 0.20 wt% to less than or equal to 0.40 wt%, from greater than or equal to 0.25 wt% to less than or equal to 0.40 wt%, from greater than or equal to 0.30 wt% to less than or equal to 0.40 wt%, from greater than or equal to 0.05 wt% to less than or equal to 0.30 wt%, from greater than or equal to 0.10 wt% to less than or equal to 0.30 wt%, from greater than or equal to 0.20 wt% to less than or equal to 0.30 wt%, from greater than or equal to 0.25 wt% to less than or equal to 0.30 wt%, from greater than or equal to 0.05 wt% to less than or equal to 0.25 wt%, from greater than or equal to 0.10 wt% to less than or equal to 0.25 wt%, from greater than or equal to 0.20 wt% to less than or equal to 0.25 wt%, from greater than or equal to 0.05 wt% to less than or equal to 0.20 wt%, from greater than or equal to 0.10 wt% to less than or equal to 0.20 wt%, or from greater than or equal to 0.05 wt% to less than or equal to 0.10 wt%.
[0065] In some embodiments, the dentifrice formulation may include other active materials for preventing or treating oral hard or soft tissue disorders. These active materials may include antibacterial agents or anti-stain agents, etc. Embodiments of the dentifrice formulation contain other active materials in an amount greater than or equal to 0.05% by weight and less than or equal to 0.50% by weight, such as greater than or equal to 0.10% by weight and less than or equal to 0.50% by weight, greater than or equal to 0.20% by weight and less than or equal to 0.50% by weight, greater than or equal to 0.25% by weight and less than or equal to 0.50% by weight, greater than or equal to 0.30% by weight and less than or equal to 0.50% by weight, greater than or equal to 0.40% by weight and less than or equal to 0.50% by weight, greater than or equal to 0.05% by weight and less than or equal to 0.40% by weight, greater than or equal to 0.10% by weight and less than or equal to 0.40% by weight, greater than or equal to 0.20% by weight and less than or equal to 0.40% by weight, greater than or equal to 0.25% by weight and less than or equal to 0.40% by weight, greater than or equal to 0.05% by weight and less than or equal to 0.30% by weight, greater than or equal to 0.10% by weight and less than or equal to 0.30% by weight, greater than or equal to 0.20% by weight and less than or equal to 0.30% by weight, greater than or equal to 0.25% by weight and less than or equal to 0.30% by weight, greater than or equal to 0.05% by weight and less than or equal to 0.25% by weight, greater than or equal to 0.10% by weight and less than or equal to 0.25% by weight, greater than or equal to 0.20% by weight and less than or equal to 0.25% by weight, greater than or equal to 0.05% by weight and less than or equal to 0.20% by weight, greater than or equal to 0.10% by weight and less than or equal to 0.20% by weight, or greater than or equal to 0.05% by weight and less than or equal to 0.10% by weight.
[0066] Embodiments of the aqueous dentifrice formulation contain greater than or equal to 2% by weight and less than or equal to 15% by weight of bioactive glass, greater than or equal to 30% by weight and less than or equal to 45% by weight of a solvent (water), greater than or equal to 40% by weight and less than or equal to 50% by weight of a humectant, greater than or equal to 0.2% by weight and less than or equal to 1.0% by weight of fluoride ions, greater than or equal to 0.5% by weight and less than or equal to 5.0% by weight of a flavoring agent, greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight of a surfactant, greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of a sweetening agent, greater than or equal to 2% by weight and less than or equal to 8% by weight of an abrasive, and greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight of a whitening agent.
[0067] Examples of non-aqueous dentifrice formulations include bioactive glass in an amount greater than or equal to 2% by weight and less than or equal to 15% by weight, a solvent (glycerol) in an amount greater than or equal to 50% by weight and less than or equal to 75% by weight, a humectant in an amount greater than or equal to 15% by weight and less than or equal to 20% by weight, fluoride ions in an amount greater than or equal to 0.2% by weight and less than or equal to 1.0% by weight, a flavoring agent in an amount greater than or equal to 0.5% by weight and less than or equal to 5.0% by weight, a surfactant in an amount greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight, a sweetening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight, an abrasive in an amount greater than or equal to 2% by weight and less than or equal to 8% by weight, and a whitening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight.
[0068] A first aspect includes a dentifrice formulation comprising: a solvent; a humectant; and bioactive glass, wherein the bioactive glass comprises: SiO2 in an amount greater than or equal to 15% by weight and less than or equal to 45% by weight, CaO in an amount greater than or equal to 30% by weight and less than or equal to 60% by weight, P2O5 in an amount greater than or equal to 8% by weight and less than or equal to 30% by weight, and ZrO2 in an amount greater than or equal to 2% by weight and less than or equal to 15% by weight.
[0069] A second aspect includes the dentifrice formulation of the first aspect, wherein the bioactive glass comprises: SiO2 in an amount greater than or equal to 20.0% by weight and less than or equal to 39.5% by weight; MgO in an amount greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight; CaO in an amount greater than or equal to 32.5% by weight and less than or equal to 47.0% by weight; SrO in an amount greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight; ZnO in an amount greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight; P2O5 in an amount greater than or equal to 9.5% by weight and less than or equal to 24.5% by weight; and ZrO2 in an amount greater than or equal to 4.0% by weight and less than or equal to 10.0% by weight.
[0070] A third aspect includes the dentifrice formulation of the first or second aspect, wherein the weight loss of the bioactive glass after 7 days of exposure in deionized water is less than or equal to 5% by weight.
[0071] A fourth aspect includes the dentifrice formulation of any one of the first to third aspects, wherein the solvent is an aqueous solvent.
[0072] A fifth aspect includes the dentifrice formulation of any one of the first to third aspects, wherein the solvent is a non-aqueous solvent.
[0073] A sixth aspect includes the dentifrice formulation of the fifth aspect, wherein the solvent is glycerol.
[0074] The seventh aspect includes a dentifrice formulation according to any one of the first to sixth aspects, wherein the dentifrice formulation comprises: a solvent in an amount of greater than or equal to 1% by weight and less than or equal to 20% by weight; a humectant in an amount of greater than or equal to 2% by weight and less than or equal to 50% by weight; and bioactive glass in an amount of greater than or equal to 1% by weight and less than or equal to 20% by weight.
[0075] The eighth aspect includes a dentifrice formulation according to any one of the first to seventh aspects, wherein the humectant is a short-chain polyol selected from the group consisting of glycerol, sorbitol, propylene glycol, and polyethylene glycol.
[0076] The ninth aspect includes a dentifrice formulation according to any one of the first to eighth aspects, which further comprises one or more of a fluoride ion source, a flavoring agent, a surfactant, a sweetening agent, a whitening agent, and an abrasive.
[0077] The tenth aspect includes the dentifrice formulation of the ninth aspect, wherein the dentifrice formulation comprises a fluoride ion source selected from the group consisting of sodium fluoride, potassium fluoride, ammonium fluoride, monofluorophosphate, and mixtures of the foregoing.
[0078] The eleventh aspect includes the dentifrice formulation of the tenth aspect, wherein the dentifrice formulation comprises fluoride ions in an amount of greater than or equal to 0.01% by weight and less than or equal to 1.00% by weight.
[0079] The twelfth aspect includes the dentifrice formulation of the ninth to eleventh aspects, wherein the dentifrice formulation comprises a flavoring agent in an amount of greater than or equal to 0.05% by weight and less than or equal to 5.00% by weight.
[0080] The thirteenth aspect includes the dentifrice formulation of any one of the ninth to twelfth aspects, wherein the dentifrice formulation comprises a surfactant selected from the group consisting of sodium lauryl sulfate, poloxamer, and mixtures of the foregoing.
[0081] The fourteenth aspect includes the dentifrice formulation of the thirteenth aspect, wherein the dentifrice formulation comprises a surfactant in an amount of greater than or equal to 0.1% by weight and less than or equal to 5.0% by weight.
[0082] The fifteenth aspect includes the dentifrice formulation of any one of the ninth to fourteenth aspects, wherein the dentifrice formulation comprises a sweetening agent in an amount of greater than or equal to 0.1% by weight and less than or equal to 5.0% by weight.
[0083] The sixteenth aspect includes the dentifrice formulation of any one of the ninth to fifteenth aspects, wherein the dentifrice formulation comprises a whitening agent selected from the group consisting of titanium dioxide, hydrogen peroxide, sodium tripolyphosphate, and mixtures of the foregoing.
[0084] The seventeenth aspect includes the dentifrice preparation of the sixteenth aspect, wherein the dentifrice preparation contains a whitening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 2.0% by weight.
[0085] The eighteenth aspect includes the dentifrice preparation of any one of the ninth to seventeenth aspects, wherein the dentifrice preparation contains an abrasive selected from the group consisting of silica, zinc orthophosphate, sodium bicarbonate, alumina, calcium carbonate, calcium pyrophosphate, and mixtures of the foregoing.
[0086] The nineteenth aspect includes the dentifrice preparation of the eighteenth aspect, wherein the dentifrice preparation contains an abrasive in an amount greater than or equal to 0.1% by weight and less than or equal to 20.0% by weight.
[0087] The twentieth aspect includes the dentifrice preparation of any one of the first to nineteenth aspects, wherein the dentifrice preparation contains: bioactive glass in an amount greater than or equal to 2% by weight and less than or equal to 15% by weight; a solvent in an amount greater than or equal to 30% by weight and less than or equal to 45% by weight; a humectant in an amount greater than or equal to 40% by weight and less than or equal to 50% by weight; fluoride ions in an amount greater than or equal to 0.2% by weight and less than or equal to 1.0% by weight; a flavoring agent in an amount greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight; a surfactant in an amount greater than or equal to 0.5% by weight and less than or equal to 1.5% by weight; a sweetening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight; an abrasive in an amount greater than or equal to 2% by weight and less than or equal to 8% by weight; and a whitening agent in an amount greater than or equal to 0.1% by weight and less than or equal to 0.5% by weight.
[0088] Examples
[0089] The embodiments will be further illustrated by the following examples.
[0090] Example 1
[0091] Twelve bioactive glass samples according to the embodiments disclosed and described herein were prepared by conventional glass melting and forming techniques. Then the density, annealing point, and refractive index of the twelve samples were compared with those of the conventional glass composition 45S5 for comparison. The compositions of 45S5 and the twelve samples are provided in Table 1 below. The annealing points and refractive indices of the twelve samples and 45S5 are also shown in Table 1.
[0092] Table 1
[0093]
[0094] Table 1 (continued)
[0095]
[0096] Example 2
[0097] The bioactive glass composition of Sample 9 from Example 1 was ground into bioactive glass particles having a particle size distribution D99 of less than 10 μm. The weight of the bioactive glass particles was measured to obtain an initial weight. The bioactive glass particles were then soaked in deionized water for 7 days. The weight of the bioactive glass particles was measured after 1 day in water, after 4 days in water, and after 7 days in water. The weights of the glass particles after 1 day, 4 days, and 7 days in water were compared to the initial weight to determine the percentage weight loss on day 1, day 4, and day 7.
[0098] The conventional 45S5 was also subjected to the above weight loss measurement. The results of this weight loss test are provided in Figure 1 . As Figure 1 shown, the bioactive glass of Sample 9 had a weight loss of less than 2.5% and was close to 0% even after 7 days of soaking in water, while the 45S5 had a weight loss of nearly 6% after only 1 day of soaking in water. This indicates that the bioactive glass of Sample 9 has much better durability in water than 45S5 and is thus suitable for aqueous dentifrice formulations.
[0099] Example 3
[0100] The bioactive glass composition of Sample 9 from Example 1 was ground into bioactive glass particles having a particle size distribution D99 of less than 10 μm. The weight of the bioactive glass particles was measured to obtain an initial weight. The bioactive glass particles were then soaked in artificial saliva manufactured by Modus Laboratories water for 7 days. The weight of the bioactive glass particles was measured after 1 day in artificial saliva, after 4 days in artificial saliva, and after 7 days in artificial saliva. The weights of the glass particles after 1 day, 4 days, and 7 days in artificial saliva were compared to the initial weight to determine the percentage weight loss on day 1, day 4, and day 7.
[0101] The conventional 45S5 was also subjected to the above weight loss measurement. The results of this weight loss test are provided in Figure 2 . As Figure 2 shown, the bioactive glass of Sample 9 had a weight loss of less than 2.5% and was close to 0% even after 7 days of soaking in artificial saliva, while the 45S5 had a weight loss of nearly 6% after only 1 day of soaking in artificial saliva. This indicates that the bioactive glass of Sample 9 has much better durability in artificial saliva than 45S5 Much better durability and is thus more suitable for non-aqueous dentifrice formulations than 45S5 Bioglass.
[0102] Example 4
[0103] The bioactive glass composition of Sample 9 from Example 1 was ground into bioactive glass particles having a particle size distribution of less than 10 μm. The bioactive glass particles were then immersed in artificial saliva manufactured by Modus Laboratories. Scanning electron microscope (SEM) images were obtained before the start of immersion, after 1 day of immersion in artificial saliva, after 2 days of immersion in artificial saliva, after 3 days of immersion in artificial saliva, after 4 days of immersion in artificial saliva, and after 7 days of immersion in artificial saliva. The SEM images are provided in Figure 3 as Figure 3 shown. Within 2 days after immersion in artificial saliva, the formation of dispersed crystals was observed. The number and size of the crystals increased with time. After 4 days, the entire surface of the bioactive glass particles was covered with a well-developed crystalline phase.
[0104] For comparison, 45S5 particles were immersed in artificial saliva manufactured by Modus Laboratories. SEM images were obtained before the start of immersion, after 1 day of immersion in artificial saliva, after 4 days of immersion in artificial saliva, and after 7 days of immersion in artificial saliva. The SEM images are provided in Figure 4 as Figure 4 shown. As shown, the surface morphology of 45S5
[0105] did not change after immersion for up to 7 days.
[0105] To determine the phase of the crystalline structure formed on the surface of the bioactive glass of Sample 9 from Example 1, X-ray diffraction (XRD) was performed on the bioactive glass of Sample 9 from Example 1 after immersion in artificial saliva for 7 days. Similarly, XRD was performed on a 45S5 sample after immersion in saliva for 7 days. The XRD data of the bioactive glass of Sample 9 from Example 1 and 45S5 are shown in Figure 5 . Figure 5 The XRD results in showed that the crystals formed in the bioactive glass of Sample 9 from Example 1 were hydroxyapatite, while no detectable crystalline phase was observed in 45S5 . The bioactive glass of Sample 9 from Example 1 exhibited a significant change in bioactivity, which may be significantly beneficial for treating cavities and allergies.
[0106] In addition to Figure 5 the XRD data shown, additional XRD data of the bioactive glass of Sample 9 from Example 1 were collected and are shown inFigure 6 In. As Figure 6 shown, six XRD patterns were collected. That is, XRD of the bioactive glass of sample 9 from Example 1 was measured as in the as-made form, after 1 day in artificial saliva, after 2 days in artificial saliva, after 3 days in artificial saliva, after 4 days in artificial saliva, and after 7 days in artificial saliva. Figure 6 The XRD patterns in showed that apatite formation occurred on the bioactive glass of sample 9 from Example 1 after 4 days of immersion in artificial saliva, and no significant additional apatite formation occurred between the 4th and 7th days of immersion in artificial saliva. This indicates an increase in the bioactivity of the bioactive glass of sample 9 from Example 1.
[0107] Example 5
[0108] Additional tests were conducted to determine the corrosion of the bioactive glass of sample 9 from Example 1 compared to 45S5 By immersing the bioactive glass of sample 9 from Example 1 and 45S5 in artificial saliva containing 28 ppm Na + 、80 ppm K + and 6 ppm Mg 2+ for seven days for the initial test. The pH of this artificial saliva was 7.1. XRD data were collected for the as-made samples, after 1 day of immersion in artificial saliva, after 4 days of immersion in artificial saliva, after 7 days of immersion in artificial saliva, after 14 days of immersion in artificial saliva, after 21 days of immersion in artificial saliva, and after 30 days of immersion in artificial saliva.
[0109] 45S5 The XRD data of was shown in Figure 7 and indicated that even before immersion in artificial saliva, natrite (Na2CO3) was present on the surface of 45S5 and only non-bioactive calcite (CaCO3) was formed on 45S5 after 30 days of immersion in artificial saliva. Therefore, 45S5 is not particularly bioactive.
[0110] The XRD data of the bioactive glass of sample 9 from Example 1 are shown in Figure 8 and confirmed the formation of hydroxyapatite on the bioactive glass of sample 9 from Example 1 within seven days or less as shown in the above examples.
[0111] Example 6
[0112] The corrosion was also tested using artificial saliva manufactured by Modus Laboratories. Bioactive glass as-made and 45S5 as-made from Sample 9 of Example 1 were collected. XRD data of were obtained for the bioactive glass and 45S5 from Sample 9 of Example 1. Then, the bioactive glass and 45S5 from Sample 9 of Example 1
[0113] Figure 9 were immersed in artificial saliva manufactured by Modus Laboratories for seven days, and XRD data of each sample were collected after immersion.
[0114] Figure 10 The XRD data of the bioactive glass from Sample 9 of Example 1 are shown. This XRD data confirmed the formation of apatite within seven days of immersion as shown in the previous examples, and no nitrite was formed as calcite. In addition, the bioactive glass from Sample 9 of Example 1 showed no surface corrosion after one year of storage. The XRD data of 45S5 are shown and indicate that natroalunite was detected in as-made 45S5 only a few days after the powder was prepared, which indicates surface corrosion. In addition, no apatite was formed in 45S5.
[0115] Example 7
[0116] The effect of the bioactive glass and 45S5 from Sample 9 of Example 1 on the pH of artificial saliva was also studied.
[0117] The bioactive glass from Sample 9 of Example 1 was immersed in deionized water (referred to as "H2O") for seven days, in artificial saliva manufactured by Modus Laboratories (referred to as "AS1") for seven days, and in artificial saliva containing 28 ppm Na + , 80 ppm K + and 6 ppm Mg 2+ with a pH of 7.1 (referred to as "AS2") for seven days. The pH of H2O, AS1, and AS2 was measured before (referred to as Day 0 in the figure) and daily for seven days after the bioactive glass from Sample 9 of Example 1. The results of this test are shown in Figure 11 .
[0118] 45S5 was immersed in H2O for seven days, in AS1 for seven days, and in AS2 for seven days. The pH of H2O, AS1, and AS2 was measured before (referred to as day 0 in the figure) and daily for seven days afterwards. The results of this test are shown in Figure 12 below.
[0119] For the bioactive glass of sample 9 from Example 1 and 45S5 For both, the pH of each solution (H2O, AS1, and AS2) increased rapidly after the addition of the glass. After soaking for approximately one day, the pH of each solution stabilized and remained relatively constant over the next six days. The bioactive glass of sample 9 from Example 1 showed a smaller pH increase than 45S5 and specifically, the bioactive glass of sample 9 from Example 1 showed the smallest pH increase in AS1, while 45S5 showed a larger pH increase than the bioactive glass of sample 9 from Example 1 in each of H2O, AS1, and AS2, and specifically in AS2.
[0120] Example 8
[0121] The normalized losses of various components in AS1 of the bioactive glass of sample 9 from Example 1 and 45S5 were also studied. The bioactive glass of sample 9 from Example 1 (referred to as "glass A" in the figure) and 45S5
[0122] were soaked in AS1 for seven days. The normalized losses of sodium and silicon of 45S5 were measured (mg / m 2 ) and the normalized losses of calcium and silicon of the bioactive glass of sample 9 from Example 1 were measured (the bioactive glass of sample 9 from Example 1 does not contain sodium).
[0123] Figure 13 The results of this test are shown. As Figure 13 shown, the bioactive glass of sample 9 from Example 1 showed extremely small normalized losses of calcium and silicon, while 45S5 showed much larger normalized silica losses and extremely high normalized sodium losses. The significant normalized sodium loss in 45S5 indicates that this glass dissolves much faster than the bioactive glass of sample 9 from Example 1, and the higher normalized silicon loss in 45S5 indicates that even the glass matrix reacts in artificial saliva. In contrast, the reactivity of the bioactive glass of sample 9 from Example 1 is much lower.
[0124]
[0124] The normalized losses were calculated by Equation 1 below:
[0125]
[0126] where C i,t is the concentration of element i at time t, C0 is the concentration of the blank solution, V is the volume of the solution, SSA is the specific surface area (measured by BET), m is the starting sample mass, and f i is the mass fraction of element i.
[0127] Example 9
[0128] The bioactive glass of sample 9 from Example 1 and 45S5 were also studied for the normalized losses of various components in AS2.
[0129] The bioactive glass of sample 9 from Example 1 (referred to as "Glass A" in the figure) and 45S5 were immersed in AS2 for thirty days. The normalized losses of sodium, silicon, and calcium of 45S5 (mg / m 2 ) were measured, and the normalized losses of calcium and silicon of the bioactive glass of sample 9 from Example 1 were measured (the bioactive glass of sample 9 from Example 1 does not contain sodium).
[0130] Figure 14 The results of this test are shown. As Figure 14 shown, the bioactive glass of sample 9 from Example 1 showed extremely small normalized losses of calcium and silicon, while 45S5 showed much greater normalized silica loss and extremely high normalized sodium loss. The significant normalized sodium loss in 45S5 indicates that this glass dissolves much faster than the bioactive glass of sample 9 from Example 1, and the higher normalized silicon loss in 45S5 indicates that even the glass matrix reacts in artificial saliva. In contrast, the bioactive glass of sample 9 from Example 1 has much lower reactivity.
[0131] The normalized loss of each component was calculated using Equation 1 from Example 8.
[0132] Example 10
[0133] The bioactive glass of sample 9 from Example 1 and 45S5 were further studied for the normalized silicon loss in H2O, AS1, and AS2.
[0134] The bioactive glass of sample 9 from Example 1 (referred to as "Glass A" in the figure) and 45S5 were immersed in H2O, AS1, and AS2 for seven days. The normalized silicon losses of the bioactive glass of sample 9 from Example 1 and 45S5 were measured Normalized silicon loss (mg / m 2 ).
[0135] Figure 15 Show the results of this test. As Figure 15 shown, the bioactive glass of sample 9 from Example 1 shows minimal normalized silicon loss in each of H2O, AS1, and AS2. In contrast, 45S5 shows significant normalized silicon loss in each of H2O, AS1, and AS2. The greater normalized silicon loss in 45S5 indicates increased reactivity of the glass and that even the glass matrix reacts. Without being bound by any particular theory, it is believed that the high calcium concentration in the bioactive glass of sample 9 from Example 1 provides low reactivity.
[0136] Calculate the normalized loss of each component using Equation 1 from Example 8.
[0137] Example 11
[0138] Further investigated the water durability of the bioactive glass of sample 9 from Example 1 and 45S5 .
[0139] Performed an ISO 719 test on the bioactive glass of sample 9 from Example 1 (referred to as "Glass A" in the figure) and 45S5 to determine the hydrolytic resistance of glass particles (300 μm to 425 μm) in water at 98 °C for 1 hour. Figure 16 Show the results of this test.
[0140] As Figure 16 shown, the bioactive glass of sample 9 from Example 1 was rated HGB 3, and 45S5 was rated HGB 5, indicating a significant increase in the water durability of the bioactive glass of sample 9 from Example 1 compared to 45S5 .
[0141] Example 12
[0142] Constitute twelve aqueous dentifrice formulations using the bioactive glass sample 9 from Example 1 above. The remaining components of the aqueous dentifrice formulations are provided in Table 2 below. It should be noted that glycerol is used as a humectant in the formulations in Table 2.
[0143] Table 2
[0144]
[0145]
[0146] Table 2 (continued)
[0147] 8 9 10 11 12 Bioactive glass 15 2 5 10 15 Water 31.38 44.24 41.24 36.24 31.24 Sorbitol 26 26 26 26 26 Glycerol 20 20 20 20 20 Sodium monofluorophosphate 0 0 0 0 0 Sodium fluoride 0.32 0 0 0 0 Stannous fluoride 0 0.46 0.46 0.46 0.46 Flavoring agent 1 1 1 1 1 Sodium lauryl sulfate 1 1 1 1 1 Sweetening agent 0.2 0.2 0.2 0.2 0.2 Titanium dioxide 0.1 0.1 0.1 0.1 0.1 Silicon dioxide 5 5 5 5 5 Total 100 100 100 100 100
[0148] Each of these dentifrice formulations has a good taste and stability over time. The formulations partially include bioactive glass, which can be used to treat or prevent various oral conditions through enamel remineralization and carious lesion remineralization.
[0149] Example 13
[0150] Twelve non-aqueous dentifrice formulations were constituted using bioactive glass sample 9 from Example 1 above. The remaining components of the aqueous dentifrice formulations are provided in Table 3 below. It should be noted that glycerol was used as the solvent in the non-aqueous dentifrice formulations.
[0151] Table 3
[0152] Ingredient 1 2 3 4 5 6 7 Bioactive glass 2 5 10 15 2 5 10 Glycerol 69.6 66.6 61.6 56.6 70.38 67.38 62.38 Polyethylene glycol 20 20 20 20 20 20 20 Sodium monofluorophosphate 1.1 1.1 1.1 1.1 0 0 0 Sodium fluoride 0 0 0 0 0.32 0.32 0.32 Stannous fluoride 0 0 0 0 0 0 0 Flavoring agent 1 1 1 1 1 1 1 Sodium lauryl sulfate 1 1 1 1 1 1 1 Sweetening agent 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Titanium dioxide 0.1 0.1 0.1 0.1 0.1 0.1 0.1 Silicon dioxide 5 5 5 5 5 5 5 Total 100 100 100 100 100 100 100
[0153] Table 3 (continued)
[0154] Ingredient 8 9 10 11 12 Bioactive glass 15 2 5 10 15 Glycerol 57.38 70.24 67.24 62.24 57.24 Polyethylene glycol 20 20 20 20 20 Sodium monofluorophosphate 0 0 0 0 0 Sodium fluoride 0.32 0 0 0 0 Stannous fluoride 0 0.46 0.46 0.46 0.46 Flavoring agent 1 1 1 1 1 Sodium lauryl sulfate 1 1 1 1 1 Sweetening agent 0.2 0.2 0.2 0.2 0.2 Titanium dioxide 0.1 0.1 0.1 0.1 0.1 Silicon dioxide 5 5 5 5 5 Total 100 100 100 100 100
[0155] Each of these dentifrice formulations has a good taste and stability over time. The formulations partially include bioactive glass, which can be used to treat or prevent various oral conditions through enamel remineralization and carious lesion remineralization.
[0156] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Accordingly, this specification is intended to cover modifications and variations of the various embodiments described herein, provided that such modifications and variations fall within the scope of the appended claims and their equivalents.
Claims
1. A dentifrice preparation, the dentifrice preparation comprising: A solvent; A humectant; and Bioactive glass, wherein the bioactive glass comprises: SiO2 greater than or equal to 15% by weight and less than or equal to 45% by weight, CaO greater than or equal to 30% by weight and less than or equal to 60% by weight, P2O5 greater than or equal to 8% by weight and less than or equal to 30% by weight, and ZrO2 greater than or equal to 2% by weight and less than or equal to 15% by weight.
2. The dentifrice preparation according to claim 1, wherein the bioactive glass comprises: SiO2 greater than or equal to 20.0% by weight and less than or equal to 39.5% by weight; MgO greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight; CaO greater than or equal to 32.5% by weight and less than or equal to 47.0% by weight; SrO greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight; ZnO greater than or equal to 0.0% by weight and less than or equal to 14.5% by weight; P2O5 greater than or equal to 9.5% by weight and less than or equal to 24.5% by weight; and ZrO2 greater than or equal to 4.0% by weight and less than or equal to 10.0% by weight.
3. The dentifrice preparation according to claim 1, wherein after 7 days of exposure in deionized water, the weight loss of the bioactive glass is less than or equal to 5% by weight.
4. The dentifrice preparation according to claim 1, wherein the solvent is an aqueous solvent.
5. The dentifrice preparation according to claim 1, wherein the solvent is a non-aqueous solvent.
6. The dentifrice preparation according to claim 5, wherein the solvent is glycerol.
7. The dentifrice preparation according to claim 1, wherein the dentifrice preparation comprises: A solvent greater than or equal to 1% by weight and less than or equal to 20% by weight; A humectant greater than or equal to 2% by weight and less than or equal to 50% by weight; and Bioactive glass greater than or equal to 1% by weight and less than or equal to 20% by weight.
8. The dentifrice preparation according to claim 1, wherein the humectant is a short-chain polyol selected from the group consisting of glycerol, sorbitol, propylene glycol, and polyethylene glycol.
9. The dentifrice preparation according to claim 1, the dentifrice preparation further comprising one or more of a fluoride ion source, a flavoring agent, a surfactant, a sweetening agent, a whitening agent, and an abrasive.
10. The dentifrice preparation according to claim 9, wherein the dentifrice preparation comprises a fluoride ion source selected from the group consisting of sodium fluoride, potassium fluoride, ammonium fluoride, monofluorophosphate, and mixtures of the foregoing.
11. The dentifrice preparation according to claim 10, wherein the dentifrice preparation comprises fluoride ions greater than or equal to 0.01% by weight and less than or equal to 1.00% by weight.
12. The dentifrice preparation according to claim 9, wherein the dentifrice preparation comprises a flavoring agent greater than or equal to 0.05% by weight and less than or equal to 5.00% by weight.
13. The dentifrice preparation according to claim 9, wherein the dentifrice preparation comprises a surfactant selected from the group consisting of sodium lauryl sulfate, poloxamer, and mixtures of the foregoing.
14. The dentifrice preparation according to claim 13, wherein the dentifrice preparation comprises from 0.1% to 5.0% by weight of the surfactant.
15. The dentifrice preparation according to claim 9, wherein the dentifrice preparation comprises from 0.1% to 5.0% by weight of a sweetening agent.
16. The dentifrice preparation according to claim 9, wherein the dentifrice preparation comprises a whitening agent selected from the group consisting of titanium dioxide, hydrogen peroxide, sodium tripolyphosphate, and mixtures of the foregoing.
17. The dentifrice preparation according to claim 16, wherein the dentifrice preparation comprises from 0.1% to 2.0% by weight of the whitening agent.
18. The dentifrice preparation according to claim 9, wherein the dentifrice preparation comprises an abrasive selected from the group consisting of silica, zinc orthophosphate, sodium bicarbonate, alumina, calcium carbonate, calcium pyrophosphate, and mixtures of the foregoing.
19. The dentifrice preparation according to claim 18, wherein the dentifrice preparation comprises from 0.1% to 20.0% by weight of the abrasive.
20. The dentifrice preparation according to claim 1, wherein the dentifrice preparation comprises: from 2% to 15% by weight of bioactive glass; from 30% to 45% by weight of a solvent; from 40% to 50% by weight of a humectant; from 0.2% to 1.0% by weight of fluoride ions; from 0.5% to 1.5% by weight of a flavoring agent; from 0.5% to 1.5% by weight of a surfactant; from 0.1% to 0.5% by weight of a sweetening agent; from 2% to 8% by weight of an abrasive; and from 0.1% to 0.5% by weight of a whitening agent.
Citation Information
Patent Citations
Bioglass coated metal substrate
US4234972A
Alkali-free bioactive sol-gel compositions
US5074916A